Genetic Predisposition and Mitochondrial Dysfunction in Sudden Cardiac Death: Role of MCU Complex Genetic Variations - Haoliang Meng; Yan He; Yukun Rui; Mengqi Cai; Dongke Fu; Wanli Bi; Bin Luo; Yuzhen Gao (Cells)
Sudden cardiac death (SCD) is a major cause of cardiovascular mortality, with coronary artery disease-related SCD (SCD-CAD) being the most prevalent form. Genetic factors and mitochondrial dysfunction, particularly in calcium homeostasis, are critical in SCD-CAD. However, the specific genetic factors linked to mitochondrial dysfunction in SCD-CAD remain poorly understood. In this case-control study, we analyzed 229 SCD-CAD cases and 598 controls from a Southern Han Chinese population, focusing on 12 insertion-deletion (indel) variants across six mitochondrial calcium uniporter (MCU) complex genes. We used capillary electrophoresis-based multiplex genotyping and performed logistic regression and haplotype analyses to assess the association of these variants with SCD-CAD susceptibility. Four significant indel variants and three risk-associated haplotypes were identified. Two of these indels were previously validated in the GWAS catalog as strongly linked to cardiac disorders. Additionally, Mendelian randomization (MR) analysis revealed a causal relationship between elevated levels of the SMDT1-encoded MCU regulator and increased risks of cardiovascular diseases, including coronary atherosclerosis, myocardial infarction, and cardiomyopathy. These findings highlight the role of MCU complex variants in SCD-CAD susceptibility and suggest their potential as biomarkers for cardiovascular risk stratification. Further research with larger cohorts is needed to confirm these results and explore underlying mechanisms.